A glimpse into nursing discursive behaviour in interprofessional online learning - Loke, Jennifer Chiok-Foong; Coluquhoun, Derek; Lee, Kah Wai (Journal of nursing education and practice, 2012)
Background: The importance of interprofessional learning to provide quality patient care has resulted in the increasing use of asynchronous computer mediated conferencing in healthcare programmes within universities. The asynchronicity based on typed-written discussions in a virtual learning environment which provided flexibility in learning was used to increase opportunities for nurses and other allied healthcare professionals to participate in interprofessional learning in higher education. However, successful online learning relies on discursive practices in the virtual learning environment, embedded within discursive exchanges in practice are power relations in nursing language use; which had a negative impact on interprofessional learning and working relationships amongst nurses, between nurses and other allied healthcare professionals. This paper presents an analysis of the discursive practices of registered nurses in interprofessional learning based on asynchronous computer mediated conferencing. It aimed to ascertain if power relations were implicit in nursing language. Methods: Fairclough’s critical discourse analysis was used to analyse eight hundred and ninety typewritten online messages created in a 100% text-based online learning module at Master’s level in a University in North England between September 2004 and September 2009. Although the messages were created by 9 registered nurses and 4 other allied healthcare professionals undertaking interprofessional learning to learn about the issues surrounding e-learning in healthcare settings, this paper is part of a larger study focused on the messages by the nurses. Results: Nurses’ messages tended to appear as the first few responses in the discussion threads and their language was formal and objectifying. The genres resembled those found either in written assignment within higher education or in nursing documentation within practice. The virtual learning environment was an alternative social space for clinical practice where dominance of nurses was created, maintained and reinforced. Conclusions: Existing literature highlighted the incidents of problematic issues of interprofessional learning. In contrast, this paper explains the way nurses, through discursive practices, construct themselves in relation to their nursing and allied healthcare colleagues. Nurses need to be aware of the power-relations embedded in their language use and future research could usefully focus on the discursive aspect of interprofessional learning.
Keywords: Asynchronous computer mediated conferencing; Critical discourse analysis; Interprofessional online learning; Power-relations; Virtual learning environment